PRINCIPALS' LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND COMPETENCE ON TEACHER PERFORMANCE AND STUDENT ACHIEVEMENT - Hardiyana, Aan (Faculty of Economics and Business, University of Pasundan, 2025)
The performance of public high school students in the Bandung Raya region of West Java Province remains below optimal levels, as does the effectiveness of teachers. This study investigates how school principals' leadership, school organizational culture, teacher work motivation, and teacher competence affect teacher performance in public high schools in the Bandung Raya region. Additionally, it examines the significant influence of teacher performance on student academic achievement. A survey involving 253 public high school teachers was conducted, employing Path Analysis for data analysis. The findings reveal that school principals' leadership, school organizational culture, teacher work motivation, and teacher competence significantly impact teacher performance, both individually and collectively. Moreover, the study identifies a substantial influence of teacher performance on student academic achievement in these schools. In conclusion, the research underscores the important roles of school principals' leadership, organizational culture, teacher competence, and motivation in enhancing teacher performance, which in turn affects student academic success. This study adds valuable insights to the existing literature on the relationship between teacher performance and student achievement, particularly within public high schools.